Visual and Audio Planned-Media to Enhance Compliance and Hemoglobin Level of Anemic Pregnant Women - Rosmaria; Sri Yun Utama; Diniyati (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
Pregnant women with anemia is still globally found and it becomes a crucial problem in which most of the anemia is caused by iron deficiency The purpose of this study was to increase the compliance and hemoglobin of pregnant women seen from the number of Fe tablets consumed at Putri Ayu Public Health Center in 2020. This study used a quasi-experimental research design with pre-, post-test design with intervention and control group. The sample of each group was 35, which meant that the total sample was 70 participants. The statistical methods used were univariate and bivariate analysis and Mann Whitney to attest the effectiveness of audio-visual media to enhance anemic pregnant women’s compliance and hemoglobin level. This study obtained different mean values between control and intervention groups in consuming Fe tablets. Moreover, there was an increase of hemoglobin level of the participants. This means that mathematically it indicates that there is a difference in compliance with the consumption of Fe and HB tablets after intervention. In addition, the results also showed that health education interventions using audio-visual media was more effective in increasing compliance with pregnant women Fe tablets and Hemoglobin compared to control group with speech explanation. As resulted from the study, the audio-visual media was effectively increase anemic pregnant women’s compliance and hemoglobin level.